What factors influence the utilisation of all doses of vaccines with subsequent doses for under-five children in Ghana? - Immurana, Mustapha; Urmi, Arabi (International Journal of Medicine, 2017)
Pneumonia, Diarrhoea, Measles, Polio and Whooping Cough are major killers of children in the world. However, one of the most effective ways of preventing these diseases is through utilising completely their respective vaccines which are normally administered in doses. Therefore given that the 2014 Ghana Demographic and Health Survey (GDHS) report showed a fall in the coverage of the subsequent doses of the Pentavalent, Pneumococcal, Polio and Rotavirus vaccines for children in Ghana, this study investigated the factors that influence the Utilisation of all Doses of these vaccines as well as the Measles vaccine. Using Data from the 2014 GDHS and employing the binary probit model, the study among other findings revealed that, children from the Eastern, Northern and Western regions were found to be less probable to have received all the doses of the Polio and Pentavalent vaccines. Also unemployed mothers were found to be less likely to demand for all the doses of the Measles, Pentavalent, Pneumococcal and Rotavirus vaccines for their children. Moreover, rising age of the household head was associated with falling utilization of all the doses of the Pneumococcal, Pentavalent and Polio vaccines for children. Furthermore, children with single mothers were found to be less likely to have received all doses of both the Polio and Pentavalent vaccines. Also uneducated mothers were found to be less likely to demand for all the doses of the Polio, Pentavalent and Measles vaccines for their children relative to mothers with secondary education. In addition mothers without health insurance were found to be less likely to utilize all the doses of the Measles and Polio vaccines for their children. Therefore reinvigoration of regional centeredness of child health utilization drives, aiding single, unemployed and uneducated women as well as strengthening the free maternal health insurance registration scheme, could be effective tools in ensuring full utilisation of all doses of these vaccines.